Comparison of Bone Healing and Delayed or Nonunion Rates Between Operatively and Non- operatively Treated Displaced Zone 1 Fifth Metatarsal Fractures - C. James Kim BA; Selene G. Parekh MD, MBA; Justin Tsai MD; Joseph T. O’Neil MD; Daniel Fuchs MD; Rachel Shakked MD; Brian S. Winters MD; Joe Daniel DO; David I. Pedowitz MD, MS (Foot & Ankle Orthopaedics, 2023)
Category: Midfoot/Forefoot; Other Introduction/Purpose: Acute fractures of the proximal fifth metatarsal are one of the most common injuries to the foot, occurring in up to 70% of all metatarsal fractures1. Displaced zone 1 fractures of the fifth metatarsal with greater than 2 mm fracture gap or those comprising greater than 30% of the cubometatarsal joint warrant operative treatment with open reduction internal fixation (ORIF)2,7, as satisfactory bone healing and patient-reported outcomes have been reported previously8–13. More recently, a few studies have demonstrated good functional outcomes after conservative treatment of zone 1 fractures with initial displacement greater than 2 mm7,13. Nevertheless, the lack of comparative studies and conflicting available evidence of outcomes warrant further investigation on this topic. Methods: A chart review was conducted to identify patients with displaced zone 1 fractures of the fifth metatarsal. Age at time of injury, gender, smoking and diabetes history, were collected. Degree of fracture displacement were measured (mm) on AP, lateral, and oblique view radiographs obtained at the initial encounter. Non-operatively treated patients were instructed to weightbear as tolerated in a Controlled Ankle Motion (CAM) boot for 6 weeks. Surgically-treated patients were placed in a short-leg splint for 2 weeks, and remained non-weightbearing in a CAM boot until 6 week period. They transitioned to normal shoe wear at the 8 week postoperative period. Chart notes were reviewed to identify the time to complete healing and incidences of delayed or nonunion. Means were compared using a one-way ANOVA or Kruskal Wallis test depending on normality, and categorical variables were compared using Chi-square or Fisher’s exact test. Results: The average time to complete healing was greater in non-operatively treated patients by 3 weeks (17.1 vs. 14.1, p=0.282). 4/37 (10.8%) non-operatively treated patients experienced delayed or non-union whereas 4/38 (13.2%) operatively-treated patients experienced delayed or non-union. This difference was statistically non-significant. The average fracture displacement (mm) on the oblique view was significantly greater in operatively-treated patients (2.68 vs. 5.40, p< 0.001). For patients with fracture gaps greater than 2 mm on the oblique view, non-operatively treated patients took 20.9 weeks whereas operatively- treated patients took 11.8 weeks to reach complete healing (p < 0.01). Conclusion: Patients who were treated non-operatively for displaced zone 1 fractures of the fifth metatarsal took on average 3 weeks longer to reach complete healing than operatively-treated patients. For patients with fracture gap greater than 2 mm on the oblique view, operative treatment was associated with significantly reduced time to complete healing.